Design, displacement, migration : spatial and material histories - Lichtman, Sarah A.; Traganou, Jilly, 1966- (New York, NY : Routledge, 2024)
"Design, Displacement, Migration: Spatial and Material Histories gathers a collection of scholarly and creative voices-spanning design, art, and architectural history; design studies; curation; poetry; activism; and social sciences--to interrogate the intersections of design and displacement. The contributors foreground objects, spaces, visual, and material practices and consider design's role in the empire, the state, and various colonizing regimes in controlling the mass movement of people, things, and ideas across borders, as well as in resisting forced mobility and immobility, or enacting new possibilities. By consciously surfacing echoes, rhymes, and dissonances among varied histories, this volume highlights local specificity while also accounting for the vectors of displacement and design across borders and histories. Design, Displacement, Migration: Spatial and Material Histories shows displacement to be a lens for understanding space and materiality and vice versa, particularly within the context of modernity and colonialism. The book will be of interest to scholars working in design history, design studies, architectural history, art history, urban studies, and migration studies"--
Provisional Demos: The Spatial Agency of Tent Cities / Mabel O. Wilson -- "It was Jamaican style, and they didn't have anything like that in England": An Oral History Account of Self-fashioning in Displacement / Elli Michaela Young -- Displacement as Protest Strategy: Political Resistance and Design Activism in the 2019-2020 Anti-ELAB Hong Kong Protests / Kyle Kwok.
Includes bibliographical references and index.
Keywords: Design -- Social aspects; Place (Philosophy); Migration, Internal; Emigration and immigration